Fenthion Compound Degradation in the Pesticide Bayleton 500 ec in Sonolysis, Ozonolysis and Sonozolysis with Addition of TiO2-anatase - Sofyanita Sofyanita; Zona Octaria (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
Fenthion an active compound contained in EC 500 lebaycid pesticides that are toxic. To reduce the level of toxicity will be degradation in sonolysis, ozonolysis and sonozolysis with the addition of TiO2-anatase. Degradation results in sonolysis, ozonolysis and sonozolysis measured by UV-Vis spectrophotometer at wavelength of 400-600 nm. From the research that has been made degradation result fenthion 6 mg/L in sonolysis without addition of catalyst of 37.5% and with the addition of TiO2-anatase catalyst obtained for 65.12% of degradation for 60 minutes. In ozonolysis at the same time obtained percent degradation of 39.77% without the addition of catalyst and 81% with the addition of TiO2-anatase catalyst. Percent degradation fenthion compound without the addition of TiO2-anatase catalyst after a 60-minute sonozolysis obtained at 91.7%.